Relationship Between Physical Activity And Sleep Duration With Nutritional Status - Chanif Kurnia Sari; Diana Widya Lestari (MEDIA ILMU KESEHATAN, 2022)
Background: Adolescence is a stage towards adulthood. One of the problems that often occurs in adolescents is nutritional status problems. Good nutritional status can be seen with lifestyle in everyday life that affects the health of adolescents in their growing period. To overcome this, it is necessary to have self-awareness in adolescents in maintaining good nutritional status in improving a healthy lifestyle. Objective : To determine the corelations between physical activity and sleep duration with nutritional status in students of class 2019 Public Health Study Program at the institute health science surya global Yogyakarta in 2022. Methods : The type of research used in this research is quantitative with Cross Sectional. The population in this study was all students of the 2019 class of public health study programs with a total population of 173 respondents. The sampling technique used is Simple Random Sampling with a sample size of 64 respondents. Data were analyzed using Kendal Tau statistical test. Results: The results showed that there was a relationship between physical activity and nutritional status with a significance value of 0.02 where the significance value was <0.05. While in the second variable there is no relationship between sleep duration and nutritional status with a significance value of 0.95 where the significance value is > (0.05). Conclusion: There is a relationship between physical activity and nutritional status in students of the 2019 batch of public health study programs at STIKes Surya Global Yogyakarta. However, there is no relationship between sleep duration and nutritional status in 2019 students of the Public Health Study Program of STIKes Surya Global Yogyakarta.